(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
International trade is an important part of the global economy, which includes the exchange of services and technologies. The article describes the essence of international trade, the stages of development and its importance in addition to the definition of changes and fixed role in the field of international trade. Development in the field of services and technologies in Uzbekistan will help to study the country’s location in international trade.